İkdam Gazetesi’indeki sanat yazıları (1894-1903) - Berispek, Burcu (My University, 2004)
We searched Ikdam Newspaper's 62 articles between the years of 1894 and 1903, and we witnessed that the articles ranged from daily ewents to arts, literature, history and fine arts. In introductory part (as indicated first part) the things we experienced in our research and the information about the Ikdam Newspaper is discussed. In second part, the number and the dates of the articles, the authors of these articles are indicated as well. In the third part, we informed our readers about the authors who wrote the articles in that newspaper. In the fourth part, which is the conclusion part, summarizes the whole thesis. The original articles are enclosed also. The most common vocabularies are provided in the glossary part. The articles between 1894 and 1903 are observed and these articles revealed the point of view or the aspect about the art in that area. In addition to this, these articles inform us about the art in local area and abroad. This is a great resource for the ones who want to search about this period.

Günlük hadiselerin yanında sanattan, edebiyata, tarihten güzel sanatlara kadar birçok konuda bilgi edindiğimiz İkdam Gazetesinin 1894-1903 yılları arasında toplam 62 makalesini inceledik. Tezimizi 4 bölümden oluşturduk. Giriş bölümünde araştırmalar sırasında yaşadıklarımıza ve İkdam Gazetesi'ne değindik. İkinci bölümde makaleleri tarih, numara ve yazarları ile belirttik. 3. Bölümde makalelerini incelediğimiz yazarlar hakkında bilgi verdik. 4. bölümde ise sonuç bölümü yer aldı. İncelediğimiz makalelerin asılları en sonra ekler bölümünde sunuldu. Sıkça karşılaştığımız Osmanlıca kelimelere sözlük bölümünde yer verdik. 1894-1903 yılları arasında incelediğimiz bu makaleler dönemin sanata bakışını ortaya koymakta yurtiçi ve yurtdışında sanat ile ilgili önemli haberler vermekte ve konu ile ilgili araştıra yapacaklar için önemli bir kaynak oluşturmaktadır.
Keywords: Sanat, Türk